Clinical-constitutional features of patients with ischemic stroke at toxic encephalopathy - Ye. A. Kladova (Бюллетень сибирской медицины)
Neurological, psychological, anthropological, biochemical, and neurovisualization statuses have been studied in 200 alcohol abused patients after acute cerebrovascular pathology. It is shown that the groups of alcohol-abused patients show a more serious clinical pattern compared to the groups of patients free of alcohol dependence.